Traditional Chinese medicine constitution and sarcopenia: a cross-sectional study - Wang, Chi; Zhang, He; Nie, Xin; Ding, Fei; Liu, Qianhui; Hou, Lisha; Deng, Yiping; Ye, Wenbin; Yue, Jirong; He, Yong (Frontiers in Public Health, 2024)
Objective Sarcopenia is a gradually advancing systemic disorder affecting skeletal muscles, primarily distinguished by diminished muscle mass and functional decline.As of present, a universally accepted diagnostic criterion for sarcopenia has yet to be established. From the perspective of the constitution theory in traditional Chinese medicine (TCM), the Yin-deficiency constitution is believed to have a significant correlation with the development of sarcopenia. The primary objective of this study was to examine the potential association between sarcopenia and Yin-deficiency constitution.Methods The present study is a cross-sectional analysis. The Asian Working Group for Sarcopenia (AWGS) recommended a diagnostic criterion for sarcopenia. A total of 141 participants over 50 years of age were diagnosed with sarcopenia. To determine the constitution of each patient, classification and determination standards were used in traditional Chinese medicine. In this study, a combination of logistic regression and propensity score matching (PSM) was employed to analyze a dataset comprising 1372 eligible observations. The diagnostic efficacy of the test in distinguishing sarcopenia was assessed through receiver operating characteristic (ROC) curve analysis.The relationship between Yin-deficiency constitution and sarcopenia was examined using logistic regression analysis. In the crude model, the odds ratio (OR) was found to be 3.20 (95% confidence interval [CI]: 1.70-6.03). After adjusting for various confounding factors, including gender, sex, 6 m walking test/(m/s), SMI, and maximum grip strength/kg, the OR increased to 9.70 . The associations between seven other biased traditional Chinese medicine (TCM) constitutions and sarcopenia were not found to be statistically significant in the fully adjusted model. The propensity score matching (PSM) analysis yielded consistent results with the logistic regression analysis. Receiver operating characteristic (ROC) curve analysis showed that the AUC of the Yin-deficiency constitution combined with age and gender reached 0.707. Conclusions Among the nine TCM constitutions examined, the Yin-deficiency constitution demonstrates an independent association with sarcopenia. Yin-deficiency constitution may serve as a potential risk factor for the development of sarcopenia. To establish a causal relationship, further experimental investigations are warranted. The diagnostic performance of sarcopenia is effectively demonstrated by the Yin-deficiency constitution combined with age and gender.